2021
DOI: 10.1021/acsestengg.1c00121
|View full text |Cite
|
Sign up to set email alerts
|

Undiscovered Multiple Roles of Multivalent Cations in the Pollutant Removal from Actual Water by Persulfate Activated by Carbon Materials

Abstract: Enormous works have focused on the influence of natural organic matter (NOM) and anions (e.g., Cl − and HCO 3 − ) on the pollutant removal efficiency by persulfate activation technologies. However, the impact of multivalent cations in actual water, e.g., Ca 2+ , on the pollutant removal has been overlooked in past research. In this work, we surprisingly found that pollutant degradation by the carbon materials activating persulfate in some actual water (e.g., groundwater) was higher than that in the buffer solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…12 To verify whether different cations in chloride solutions affect the electron transfer between H 2 O 2 and catalyst, LSV was used to measure the current response in the systems containing phenol, H 2 O 2 and 15 000 mg L −1 salt (MgCl 2 , CaCl 2 , NaCl and KCl, respectively), with γ-Cu 2 (OH) 3 Cl as the working electrode and boric acid as buffer solution. 23 The curves are shown in Fig. 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…12 To verify whether different cations in chloride solutions affect the electron transfer between H 2 O 2 and catalyst, LSV was used to measure the current response in the systems containing phenol, H 2 O 2 and 15 000 mg L −1 salt (MgCl 2 , CaCl 2 , NaCl and KCl, respectively), with γ-Cu 2 (OH) 3 Cl as the working electrode and boric acid as buffer solution. 23 The curves are shown in Fig. 3.…”
Section: Resultsmentioning
confidence: 99%
“…For the measurement, phenol and H 2 O 2 were introduced into the buffer with their concentrations same as those in the activity test experiments. 23 Electrochemical impedance spectroscopy (EIS) of the reaction system was also measured on the above electrochemical workstation. The working electrode, reference electrode and counter electrode are the same as mentioned above.…”
Section: Characterizationmentioning
confidence: 99%
“…Thanks to its high efficiency and low cost, flocculation has long been applied in purifying industrial wastewaters and has been emerging as a promising technology to treat complex industrial discharges with various pollutants. However, most widely applied commercial flocculants such as inorganic salts and organic synthetic polymers tend to remain toxic metal ions and unreacted monomers in purified water after flocculation, which is harmful to human beings and can cause severe environmental issues. , Therefore, natural biopolymer flocculants such as chitosan have attracted great attention recently because of their environmentally friendliness, biodegradability, wide resource, and low cost. As one of the most abundant polysaccharides derived from chitin, , Chitosan has numerous ionizable amino groups on its backbones. , Under acidic conditions, chitosan would be protonated and become positively charged and thus can act as a cationic flocculant. , Previous studies have demonstrated their great flocculation performance to remove various pollutants from wastewater through efficient bridging and charge neutralization effects. However, as a weak basic polymer, chitosan is barely soluble in neutral and basic aqueous media, which makes it only applicable at acidic pHs below its p K a of 6.5. , To extend its pH flocculation window, chemical quaternization has been widely applied to improve the positively charged density and solubility of the resultant chitosan derivatives in various pH conditions. , While these cationic flocculants have exhibited excellent removal performance in treating the simulated wastewaters, they still suffer from insufficient flocculation performance with high dosage for treating complex industrial wastewaters. This inferior performance can be attributed to the following: (1) the high salinity of these wastewater can dramatically depress charge neutralization effects of these strong cationic flocculants to the pollutants; , (2) presence of various pollutants may further undermine their bridging effect through complicating and weakening intermolecular interactions between pollutant particles and functional groups of flocculants. , Thus, a qualified chitosan-based flocculant for industrial wastewater requires introducing special functional groups that could enable diverse interaction mechanisms in high salinity to provide strong intermolecular and interfacial interactions to effectively flocculating different pollutant components.…”
Section: Introductionmentioning
confidence: 99%
“…This inferior performance can be attributed to the following: (1) the high salinity of these wastewater can dramatically depress charge neutralization effects of these strong cationic flocculants to the pollutants; 42,43 (2) presence of various pollutants may further undermine their bridging effect through complicating and weakening intermolecular interactions between pollutant particles and functional groups of flocculants. 44,45 Thus, a qualified chitosan-based flocculant for industrial wastewater requires introducing special functional groups that could enable diverse interaction mechanisms in high salinity to provide strong intermolecular and interfacial interactions to effectively flocculating different pollutant components. Marine mussels provide a fascinating solution to this goal.…”
Section: Introductionmentioning
confidence: 99%
“…24 Nevertheless, to achieve a high level of defects, carbon materials need to have a high content of heteroatoms, which is not satisfied by common carbon materials. 25 Liu et al doped sulfur into ordered mesoporous carbons first and then pyrolyzed them to generate more defects. This approach, however, entails more complex production processes and higher costs.…”
Section: Introductionmentioning
confidence: 99%